2014
DOI: 10.12691/wjar-2-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites Contents and Antioxidant Capacities of <i>Acmella</i><i> </i><i>Oleracea</i><i>e</i> Grown under Different Growing Systems

Abstract: Acmella oleraceae (L.) R.K. Jansen (Asteraceae) is a therapeutically important medicinal plant used in traditional systems of medicine. Present study was undertaken to compare the total phenolic contents (TPC), total flavonoid contents (TFC), total antioxidant capacity (TAC) and Thin Layer Chromatography (TLC) profiles of areal parts and callus extracts of A. oleraceae grown under different growing systems (field grown, hydroponically grown and callus culture. Callus established in Murasige and Skoog (MS) medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…As spilanthol is an amphiphilic compound, 47 it can be extracted from plants using solvents that vary in polarity such as Hex 18 and MeOH:H 2 O (4:1, v/v). 48 Studies report that HPLC quantification with UV detection allows the identification of the content of spilanthol in different extracts, 24,49,50,51 as it was observed in this study. Spilanthol showed solubility in chloroform and it had its structure determined by NMR, according to the data compared in the literature.…”
Section: Discussionsupporting
confidence: 60%
“…As spilanthol is an amphiphilic compound, 47 it can be extracted from plants using solvents that vary in polarity such as Hex 18 and MeOH:H 2 O (4:1, v/v). 48 Studies report that HPLC quantification with UV detection allows the identification of the content of spilanthol in different extracts, 24,49,50,51 as it was observed in this study. Spilanthol showed solubility in chloroform and it had its structure determined by NMR, according to the data compared in the literature.…”
Section: Discussionsupporting
confidence: 60%
“…These varietal specific spots could be used for authentication of these two varieties. Thin layer chromatographic profile have been successfully used for authentication of Acmella oleraceae [22], Munronia pinnata and Andrographis paniculata [23], for authentication of field grown and hydroponically grown Acmella oleracea [24] and Gyrinops walla [25]. Essential oil content of local variety was lower (0.4 %) than the introduced variety (2.4%).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the secondary metabolites of hydroponic grown plants of Datura and Taxus can be 'milked' using hydroponic conditions and permeabilization (Gontier et al, 2002). In plants of Acmella oleraceae L (Asteraceae) growing in hydroponics, Abeysinghe et al (2014) were able to increase the total phenolics and flavonoids contents by supplying more N to the nutrient solution. Waller and Henderson (1961) and Waller and Yang (1965), who studied the biosynthetic pathway of ricinine from organic and inorganic compounds labeled with N 15 , found that the relative efficiency of incorporation of labeled compounds followed a gradient: formamide glutamine aspartate > > > NH 4 NO 3 nicotinamide (Amida-N) > > nicotinitrile KNO 3 (nitrile-N) 1-methyinicotinamida > (Amide-N) 1-methyilnicotinonitrilo > (nitrile N).…”
Section: Discussionmentioning
confidence: 99%